THE ROLE OF BREAST IMAGING MODALITIES IN THE DIAGNOSIS AND MANAGEMENT OF BENIGN BREAST DISEASES - JAIN, PIYUSH; JAIN, SUNIL (International Journal of Current Pharmaceutical Research, 2025)
Objective: Accurate diagnosis and management of benign breast diseases are crucial aspects of breast healthcare. Breast imaging modalities such as mammography, ultrasound, and magnetic resonance imaging (MRI) play a pivotal role in differentiating benign from malignant lesions and guiding appropriate management strategies. Methods: This retrospective study was conducted at [Institution Name] from January 2018 to December 2022. It involved a review of medical records, imaging results, and management outcomes of patients diagnosed with benign breast diseases. Imaging modalities included mammography, ultrasound, and MRI. The diagnostic accuracy of each modality was assessed by comparing imaging findings with histopathological results. Statistical analyses were performed using SPSS version 26.0. Results: A total of 200 patients were included, with a mean age of 45.3±12.6 y. Mammography showed a sensitivity of 85% and specificity of 78%, while ultrasound had a sensitivity of 92% and specificity of 84%. MRI exhibited the highest accuracy with a sensitivity of 95% and specificity of 90%. Combined imaging modalities achieved the highest diagnostic performance. Management strategies varied, with watchful waiting, medication, minimally invasive procedures, and surgical interventions employed based on the specific condition. Conclusion: Breast imaging modalities are indispensable in diagnosing and managing benign breast diseases. The integration of mammography, ultrasound, and MRI provides comprehensive diagnostic information, guiding optimal management strategies and improving patient outcomes. Future advancements in imaging technology promise to further enhance diagnostic capabilities.